Sex Differences in Animal Models of Traumatic Brain Injury - Rubin, Todd G (J Exp Neurosci, 2019)
Traumatic brain injury (TBI) is highly prevalent and there is currently no adequate treatment. Understanding the underlying mechanisms governing TBI and recovery remains an elusive goal. The heterogeneous nature of injury and individual’s response to injury have made understanding risk and susceptibility to TBI of great importance. Epidemiologic studies have provided evidence of sex-dependent differences following TBI. However, preclinical models of injury have largely focused on adult male animals. Here, we review 50 studies that have investigated TBI in both sexes using animal models. Results from these studies are highly variable and model dependent, but largely show females to have a protective advantage in behavioral outcomes and pathology following TBI. Further research of both sexes using newer models that better recapitulate mild and repetitive TBI is needed to characterize the nature of sex-dependent injury and recovery, and ultimately identifies targets for enhanced recovery.